Tin dioxide nanomaterial-based photocatalysts for nitrogen oxide oxidation: a review - Viet Van Pham; Hong-Huy Tran; Thao Kim Truong; Thi Minh Cao (Beilstein Journal of Nanotechnology, 2022)
Semiconducting SnO2 photocatalyst nanomaterials are extensively used in energy and environmental research because of their outstanding physical and chemical properties. In recent years, nitrogen oxide (NOx) pollutants have received particular attention from the scientific community. The photocatalytic NOx oxidation will be an important contribution to mitigate climate change in the future. Existing review papers mainly focus on applying SnO2 materials for photocatalytic oxidation of pollutants in the water, while studies on the decomposition of gas pollutants are still being developed. In addition, previous studies have shown that the photocatalytic activity regarding NOx decomposition of SnO2 and other materials depends on many factors, such as physical structure and band energies, surface and defect states, and morphology. Recent studies have been focused on the modification of properties of SnO2 to increase the photocatalytic efficiency of SnO2, including bandgap engineering, defect regulation, surface engineering, heterojunction construction, and using co-catalysts, which will be thoroughly highlighted in this review.